2021
DOI: 10.3390/photonics8010017
|View full text |Cite
|
Sign up to set email alerts
|

Study of Phase Transition in MOCVD Grown Ga2O3 from κ to β Phase by Ex Situ and In Situ Annealing

Abstract: We report the post-growth thermal annealing and the subsequent phase transition of Ga2O3 grown on c-plane sapphire substrates by metal organic chemical vapor deposition (MOCVD). We demonstrated the post-growth thermal annealing at temperatures higher than 900 °C under N2 ambience, by either in situ or ex situ thermal annealing, can induce phase transition from nominally metastable κ- to thermodynamically stable β-phase. This was analyzed by structural characterizations such as high-resolution scanning transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 20 publications
3
23
0
Order By: Relevance
“…The three peaks that were observed were similar to the results of the β-Ga 2 O 3 substrate (Figure 1). However, the TEM analysis in Figure 1d showed the result of κ-phase with the space group of Pna2 1 [4,5,10]. This metastable and transient κ-Ga 2 O 3 was also identified by Playford et al [13].…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…The three peaks that were observed were similar to the results of the β-Ga 2 O 3 substrate (Figure 1). However, the TEM analysis in Figure 1d showed the result of κ-phase with the space group of Pna2 1 [4,5,10]. This metastable and transient κ-Ga 2 O 3 was also identified by Playford et al [13].…”
Section: Resultsmentioning
confidence: 59%
“…Moreover, the relatively low thermal conductivity of Ga 2 O 3 and the problem of Ga 2 O 3 substrate cost being two orders of magnitude higher than sapphire are both currently hindering the fuller development of Ga 2 O 3 -based powered electronics. In previous studies, we showed that κ-Ga 2 O 3 (an orthorhombic polymorph which is normally considered to be transient) could be stabilized in heteroepitaxial growth on sapphire (0001) substrates by MOCVD [4][5][6][7][8][9][10][11][12]. In this work, we found that high levels of shallow acceptor p-type conduction could be achieved in such layers using silicon impurity doping under Ga rich growth conditions.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Figure 1 shows the top-view FESEM images of the Ga2O3 films on the c-plane (0001) sapphire substrates. None of the as-deposited and annealed Ga2O3 films had extended cracks after the ex situ annealing process using the RTA system [23]. The as-deposited film showed that the surface morphologies comprised fine grains tightly connected with a relatively clear boundary, as shown in Figure 1a.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the oxygen precursor, commonly used O 2 is the established choice, yet the use of N 2 O can lead to a lower background charge carrier concentration [ 21 ] and the use of water (H 2 O) vapour can potentially have a positive effect on the kinetic conditions during film growth due to the presence of hydrogen [ 20 ]. There are only a few papers reporting the use of H 2 O as an oxygen precursor; Alema et al demonstrated a reduction in carrier concentration by adding a small amount of H 2 O to the O 2 flow during the film growth [ 22 ], while Lee et al and Chen et al reported Ga 2 O 3 film growth using H 2 O as the oxygen precursor without further discussions on the choice [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%